2002
DOI: 10.1089/107555302320825183
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Degree of Complementary and Alternative Medicine Use Among Patients with Cancer

Abstract: This study is one of few studies exploring predictors for the quantity or degree of use of CAM by patients with cancer. Understanding factors related to these patients' heavier or lighter CAM use has implications for health care offerings and cancer treatment decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 32 publications
5
71
2
Order By: Relevance
“…However, some of these patients have described feeling "pushed" towards CAM as result of their beliefs about conventional cancer treatments being "toxic," "poisonous," or immunosuppressive 21,37 . Still others have turned toward CAM because of their dissatisfaction with conventional care, including the quality and quantity of their interactions with health professionals, the adverse effects of conventional treatment, and their experiences with ineffective therapies 16,35,37,44,45 . These latter patients are most at risk of abandoning conventional care in lieu of alternative treatments.…”
Section: 23mentioning
confidence: 99%
“…However, some of these patients have described feeling "pushed" towards CAM as result of their beliefs about conventional cancer treatments being "toxic," "poisonous," or immunosuppressive 21,37 . Still others have turned toward CAM because of their dissatisfaction with conventional care, including the quality and quantity of their interactions with health professionals, the adverse effects of conventional treatment, and their experiences with ineffective therapies 16,35,37,44,45 . These latter patients are most at risk of abandoning conventional care in lieu of alternative treatments.…”
Section: 23mentioning
confidence: 99%
“…Previous studies have explored only to a limited extent the prioritization of reasons that patients use in selecting IM. [13][14][15][16][17] Patients apparently combine conventional medical and CAM approaches rather than use one or the other exclusively, 18 without necessarily informing their physicians or CAM providers of the specific interventions that they use. This often results in a noncoordinated and independent default form of self-care, 19,20 which creates a relative "parallel practice" approach.…”
mentioning
confidence: 99%
“…16,[21][22][23][24][25] Yet, only 2 studies that focus on the outcomes associated with 2 IM practice models have been reported in the literature. Mulkins and Verhoef 26 described the healing experiences of 11 patients with cancer who received care in 3 different IM practices characterized as multidisciplinary.…”
mentioning
confidence: 99%
“…In the analysis of profi le of patients who used CAM, studies showed that they are adults aged between 30 and 59 years of age, 5,7,12,14,19,26,28,29,30,38,43 female, 11,20,26,27,30,41,43 with a high level of education 3,6,9,14,17,19,20,28,29 and high family income, 7,14,19,26,28,29,41 with advanced-staged cancer, 6,7,23,26,30,37,39,42 belonging to some religious group 20 and ethnically infl uenced 1,17,19,37 in relation to the alternative therapy adopted.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,24,40,45 In relation to the psychological motivation, the promotion of well-being, control of stress and improvement of life quality were described. 2,5,6,9,14,23,27,46 The technical reasons for the use of CAM in the treatment of cancer are intimately connected to the dissatisfaction with conventional treatment, 1,8,12,36,37 especially concerning side effects and the interaction that is formed with health professionals, 33 besides the autonomous, humanizing process promoted by non-conventional practices.…”
Section: Methodsmentioning
confidence: 99%